A new species of Caryodaphnopsis Airy Shaw (Lauraceae) from southeastern Yunnan, China - Liu, Bing; Yang, Yong; Ma, Keping (Phytotaxa, 2013)
After four consecutive years of field investigations in tropical forests of SE Yunnan of China, we found a Caryodaphnopsis species (Lauraceae) which is similar to C. laotica in possessing pubescent leaves, petioles and twigs, but differs from the latter by the densely pubescent ovary. As a result, a new species Caryodaphnopsis malipoensis, is described. Conservation status of the species was considered as VU D2. Illustrations and a distribution map of the new species are provided.